Cytogenetic monitoring of freshwater aquaculture in Ukraine - Glushko, Yuliia; Mruk, Antonina; Bielikova, Olena; Kozubska-Sobocinska , Anna (Problems of Environmental Biotechnology, 2021)
The results of cytogenetic analysis of freshwater aquaculture in Ukraine are presented.